A case of catecholaminergic polymorphic ventricular tachycardia masquerading as an intractable seizure - Reza Shabanian; Manizheh Ahani; Shima Zandiyeh; Aliyeh Nikdoost; Minoo Dadkhah; Parvin Akbari Asbagh; Reza Shervin Badv (Wolters Kluwer Medknow Publications, 2020)
A 5-year-old boy with the history of intractable seizure for the past 2 years was transferred to the emergency room for cardiopulmonary resuscitation because of the prolonged seizure and profound cyanosis. He was intubated and resuscitated by cardioversion for a bizarre shape ventricular tachycardia (VT). After noxious stimulation, he showed multiple polymorphic ventricular premature beats that were followed by a bidirectional VT in favor of catecholaminergic polymorphic VT. The genetic assessment was positive for CASQ2 mutation. In the follow-up, the arrhythmia was controlled by nadolol, however with a prominent neurological sequela.